Repeated MDA5 Gene Loss in Birds: An Evolutionary Perspective - Krchlíková, Veronika; Hron, Tomáš; Těšický, Martin; Li, Tao; Hejnar, Jiří; Vinkler, Michal; Elleder, Daniel (Viruses, 2021)
Two key cytosolic receptors belonging to the retinoic acid-inducible gene I (RIG-I)-like receptor (RLR) family sense the viral RNA-derived danger signals: RIG-I and melanoma differentiation-associated protein 5 (MDA5). Their activation establishes an antiviral state by downstream signaling that ultimately activates interferon-stimulated genes (ISGs). While in rare cases RIG-I gene loss has been detected in mammalian and avian species, most notably in the chicken, MDA5 pseudogenization has only been detected once in mammals. We have screened over a hundred publicly available avian genome sequences and describe an independent disruption of MDA5 in two unrelated avian lineages, the storks (Ciconiiformes) and the rallids (Gruiformes). The results of our RELAX analysis confirmed the absence of negative selection in the MDA5 pseudogene. In contrast to our prediction, we have shown, using multiple dN/dS-based approaches, that the MDA5 loss does not appear to have resulted in any compensatory evolution in the RIG-I gene, which may partially share its ligand-binding specificity. Together, our results indicate that the MDA5 pseudogenization may have important functional effects on immune responsiveness in these two avian clades.
Keywords: přirozená imunita; sekvence aminokyselin; lidé; DEAD Box Protein 58; Birds; DEAD box protein 58; ptačí proteiny; ptáci; Gene Deletion; Immunity, Innate; Humans; sekvenční seřazení; pseudogeny; fylogeneze; delece genu; zvířata; Animals; molekulární modely; Sequence Alignment; Pseudogenes; Phylogeny; Amino Acid Sequence; Models, Molecular; Avian Proteins